Fenomena Sungai di bawah Laut dalam Perspektif Al-Qur’an: Kajian Tafsir Ilmu dalam Surat Al-Furqan Ayat 53 - Andi Rosa; Siti Waspiatul Kamilah; Tazkia Nur Fateha; M. Zaky Hamdie; Imron Rosadi (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study reveals a significant correlation between the phenomenon of underwater rivers discussed in modern oceanographic studies and the scientific signs contained in Surah Al-Furqan verse 53. This verse not only illustrates the difference between two types of water, but also represents physical phenomena that can be explained scientifically, such as the existence of halocline layers and hydrogen sulfide compounds that appear in the transition area between fresh water and sea water. Both classical and contemporary interpretations show that the Qur'an implicitly conveys instructions regarding natural realities that can only be understood through a contemporary scientific approach. The scientific interpretation approach opens up integrative opportunities between divine revelation and empirical knowledge, which not only strengthens the dimension of faith but also stimulates rational, scientific, and spiritual thinking in exploring the meaning of the kauniyah verses. Thus, this study emphasizes the importance of a multidisciplinary approach in understanding the Qur'an in a way that is relevant to the dynamics of science and the challenges of the times.